2015
DOI: 10.7567/jjap.55.01ab06
|View full text |Cite
|
Sign up to set email alerts
|

Study on ozone treatment of soil for agricultural application of surface dielectric barrier discharge

Abstract: Recently, application of plasma technologies to the agricultural field has attracted much interest because residual pesticides and excessive nitrogen oxides contained in plants, soil, and groundwater have become a serious issue worldwide. Since almost all of the atmospheric discharge plasma generates ozone, the effects of ozone are among the key factors for their agricultural applications. We have proposed the use of ozone generated using surface barrier discharge plasma for soil disinfection or sterilization.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Mitsugi et al (2014) observed a marked reduction in soil pH after ozonation in a rotating quartz chamber, in agreement with our results. Several studies have demonstrated that H + , salts, and other compounds attached to soil organic matter can be released into the soil solution as a result of the oxidation of the organic matter (Ghahrchi and Rezaee, 2020;Nagatomo et al, 2015). Thus, this phenomenon may explain the observed increase in EC and water-soluble C and N upon ozonation in our study.…”
Section: Physico-chemical and Chemical Effects Of Solarization And Oz...supporting
confidence: 61%
See 1 more Smart Citation
“…Mitsugi et al (2014) observed a marked reduction in soil pH after ozonation in a rotating quartz chamber, in agreement with our results. Several studies have demonstrated that H + , salts, and other compounds attached to soil organic matter can be released into the soil solution as a result of the oxidation of the organic matter (Ghahrchi and Rezaee, 2020;Nagatomo et al, 2015). Thus, this phenomenon may explain the observed increase in EC and water-soluble C and N upon ozonation in our study.…”
Section: Physico-chemical and Chemical Effects Of Solarization And Oz...supporting
confidence: 61%
“…Ozone can contribute to the oxidation of organic compounds (i.e. pesticides) and thus facilitating further biodegradation (Nagatomo et al, 2015). Solarization increases temperature and humidity of soil (Scopa et al, 2008), thus enhancing microbial activity and the potential biodegradation of pesticides by microbial-mediated processes (Kanaan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The use of traditional chemical treatments results in groundwater pollution with consequent damage to ecosystems. Nagatomo et al [163] proposed the use of ozone generated by surface DBD for soil treatment. Their results revealed that ozone diffused well into the soil.…”
Section: Atmospheric-pressure Plasmasmentioning
confidence: 99%
“…Using plasma, nitrogen from air can be captured, held and incorporated into water. This process leads to the formation of nitrogen Water 2020, 12, 3545 2 of 15 compounds capable to sustain plants [8,18,19] and reactive compounds of oxygen utilized for the stress decrease of pathogens in the soil [20]. Plasma can be also applied for disinfection of food packaging [21].…”
Section: Introductionmentioning
confidence: 99%